Infection‐competent monkeypox virus contamination identified in domestic settings following an imported case of monkeypox into the UK. (20th July 2022) - Atkinson, Barry; Burton, Christopher; Pottage, Thomas; Thompson, Katy‐Anne; Ngabo, Didier; Crook, Ant; Pitman, James; Summers, Sian; Lewandowski, Kuiama; Furneaux, Jenna; Davies, Katherine; Brooks, Timothy; et al.
Abstract: An imported case of monkeypox was diagnosed in December 2019 in a traveller returning from Nigeria to the UK. Subsequently, environmental sampling was performed at two adjoining single‐room residences occupied by the patient and their sibling. Monkeypox virus DNA was identified in multiple locations throughout both properties, and monkeypox virus was isolated from several samples 3 days after the patient was last in these locations. Positive samples were identified following the use of both vacuum and surface sampling techniques; these methodologies allowed for environmental analysis of potentially contaminated porous and non‐porous surfaces via real‐time quantitative reverse transcriptase PCR analysis in addition to viral isolation to confirm the presence of infection‐competent virus. This report confirms the potential for infection‐competent monkeypox virus to be recovered in environmental settings associated with known positive cases and the necessity for rapid environmental assessment to reduce potential exposure to close contacts and the general public. The methods adopted in this investigation may be used for future confirmed cases of monkeypox in order to establish levels of contamination, confirm the presence of infection‐competent material and to identify locations requiring additional cleaning.